Diminished Ovarian Reserve and Endometriosis: Insult upon Injury - Shah, Divya Kelath (Seminars in Reproductive Medicine, 2013)
Endometriosis is a disease that affects a significant proportion of reproductive-age women. The impact of the disease on ovarian reserve is an important consideration when planning treatment in women who want to maintain their potential for future childbearing. The existing literature supports an adverse effect of both superficial endometriosis and ovarian endometriomas on ovulation rates, markers of ovarian reserve, and response to ovarian stimulation, although data on clinical pregnancy and live-birth rates remain inconsistent. Surgical treatment of endometriomas may further worsen ovarian responsiveness by inadvertently removing healthy ovarian tissue or compromising vascular supply to the ovary. Although the evidence overall supports a role for surgery in improving spontaneous pregnancy rates, the question of whether identification of an endometrioma warrants its excision in the subgroup of women undergoing infertility treatment remains a subject of ongoing debate. Many practitioners recommend proceeding directly to in vitro fertilization to reduce time to pregnancy, reserving surgery for women who present with large endometriomas and concomitant symptoms of pain. Further study is required as to the mechanisms by which endometriosis damages ovarian damage as well as the most appropriate treatment in various subpopulations of women with the disease.
Keywords: endometriosis; endometriomas; ovarian reserve